Increased Remyelination and Proregenerative Microglia Under Siponimod Therapy in Mechanistic Models. Issue 3 (30th May 2022) - Dietrich, Michael; Hecker, Christina; Martin, Elodie; Langui, Dominique; Gliem, Michael; Stankoff, Bruno; Lubetzki, Catherine; Gruchot, Joel; Göttle, Peter; Issberner, Andrea; Nasiri, Milad; Ramseier, Pamela; et al.
Abstract : Background and Objectives: Siponimod is an oral, selective sphingosine-1-phosphate receptor-1/5 modulator approved for treatment of multiple sclerosis. Methods: Mouse MRI was used to investigate remyelination in the cuprizone model. We then used a conditional demyelination Xenopus laevis model to assess the dose-response of siponimod on remyelination. In experimental autoimmune encephalomyelitis–optic neuritis (EAEON) in C57Bl/6J mice, we monitored the retinal thickness and the visual acuity using optical coherence tomography and optomotor response. Optic nerve inflammatory infiltrates, demyelination, and microglial and oligodendroglial differentiation were assessed by immunohistochemistry, quantitative real-time PCR, and bulk RNA sequencing. Results: An increased remyelination was observed in the cuprizone model. Siponimod treatment of demyelinated tadpoles improved remyelination in comparison to control in a bell-shaped dose-response curve. Siponimod in the EAEON model attenuated the clinical score, reduced the retinal degeneration, and improved the visual function after prophylactic and therapeutic treatment, also in a bell-shaped manner. Inflammatory infiltrates and demyelination of the optic nerve were reduced, the latter even after therapeutic treatment, which also shifted microglial differentiation to a promyelinating phenotype. Discussion: These results confirm the immunomodulatory effects of siponimod and suggest additional regenerative and promyelinating effects, which follow the dynamics of a bell-shaped curve with high being less efficient than low concentrations.